How Does Knowledge on Public Expenditures Integrate with the Design of Development Policy Operations? - Independent Evaluation Group (World Bank, Washington, DC, 2015)
Integration of knowledge with lending is an enduring theme in World Bank strategies at the corporate and country levels. It rests on the widely shared proposition that Bank lending instruments could be more relevant and produce better results if they incorporate key analytical, country level knowledge. To be successful, development interventions must be informed by evidence, and evidence comes from knowledge. This is the idea behind Bank as a ‘solutions bank,’ integrating financial instruments and knowledge products into ‘development solutions’ that deliver results. A recent Independent Evaluation Group (IEG) evaluation suggests that the Bank’s broad economic and sector work and technical assistance strongly inform Bank lending strategies (IEG 2008). PERs, for the purpose of this learning product, are identified as Bank knowledge products with a specific reference in their titles as Public Expenditure Review, whether they are multi-sector or single sector public expenditure reviews. They also include other analytical documents which deal with public expenditure issues, be they public finance reviews, studies of specific expenditure and debt issues, and even Country Economic Memoranda (CEMs) with a special focus on public expenditures. This broad definition should capture much (though not all) of the public expenditure-related analytical work at the Bank. Arguably, efficiency and allocation issues important in the design of DPOs and the reforms they support can only be addressed by such integrative, not partial or silo-type knowledge of specific subsector expenditures (e.g., tertiary education expenditure review).